A mixed‐methods, randomized controlled feasibility trial of Eye Movement Desensitization and Reprocessing (EMDR) plus Standard Care (SC) versus SC alone for DSM‐5 Posttraumatic Stress Disorder (PTSD) in adults with intellectual disabilities. Issue 4 (4th February 2019) - Karatzias, Thanos; Brown, Michael; Taggart, Laurence; Truesdale, Maria; Sirisena, Chammy; Walley, Robert; Mason‐Roberts, Susan; Bradley, Aoife; Paterson, Douglas
Abstract: Objective: To report the results of the first randomized feasibility trial of Eye Movement Desensitization and Reprocessing (EMDR) plus Standard Care (SC) versus SC alone for DSM‐5 posttraumatic stress disorder (PTSD) in adults with intellectual disabilities. Method: A total of 29 participants were randomized to either to EMDR + SC ( n  = 15) or SC ( n  = 14). Participants completed measures on traumatic stress (PCL‐C) and comorbid distress at baseline, 1 week post‐treatment and 3‐month follow‐up. Results: In the EMDR + SC group, 9 (60%) participants at post‐treatment and 7 (47%) participants at 3‐month follow‐up were diagnosis free. In SC, 4 (27%) at post‐treatment and follow‐up were diagnosis free. At post‐treatment, three participants (20%) dropped out from the EMDR + SC group, and 1 (7%) dropped out from the SC group. Conclusions: It is feasible, acceptable and potentially effective to deliver EMDR in this population group.